THE DETERMINATION OF STATE BASELINES POST-PEAT ABRASION ON BENGKALIS ISLAND AS INDONESIA'S FOREMOST ISLAND IN TERMS OF INTERNATIONAL LAW OF THE SEA PERSPECTIVE - Cahyani, Harpita Dwi; Maria Maya Lestari; Ledy Diana (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Coastal abrasion is a growing global concern, particularly for Indonesia, a country with one of the longest coastlines in the world. Abrasion poses significant challenges to coastal ecosystems and the livelihoods of local communities. Bengkalis Island, one of Indonesia's outermost and foremost islands, has experienced intensified abrasion in recent decades. Located in Riau Province and facing the Strait of Malacca, this peat-contoured island serves as a basepoint for Indonesia's archipelagic baselines. This research aims to: (1) analyze the legal implications of peat erosion on Indonesia's baselines post-erosion, and (2) describe the Indonesian government's efforts to address the issue.  This normative legal research examines the synchronization between national regulations and international standards regarding peatland conservation and erosion mitigation, particularly in strategically important foremost islands. The study reveals two key findings. First, peat abrasion on Bengkalis Island has serious legal implications for determining Indonesia's archipelagic baselines and maritime boundaries under UNCLOS 1982. Abrasion also threatens the island's status as an outermost and foremost island, potentially leading to the loss of Indonesia's rights over natural resources in the area. Failure to protect peat ecosystems may be considered a violation of Indonesia's international obligations to preserve marine and wetland environments under UNCLOS 1982 and the Ramsar Convention. Second, the Indonesian government has implemented legal and technical measures, such as issuing Government Regulation No. 57 of 2016 on Peat Ecosystem Protection and Management, constructing breakwaters, planting mangroves, and implementing the 3R program (Rewetting, Revegetation, and Revitalization) through the Peat and Mangrove Restoration Agency (BRGM). These efforts have shown positive results in reducing erosion rates and protecting coastalines.